Public perceptions of responsibility for alcohol control actions by actor type in seven countries. (January 2023) - Pettigrew, Simone; Booth, Leon; Pinho-Gomes, Ana-Catarina
Highlights: Greater implementation of evidence-based alcohol harm-reduction actions is needed. Government appetite for alcohol interventions is influenced by public support. Respondents from seven diverse countries expressed support for various actions. Support varied by country and action, but was a majority in most cases. Governments are likely to have a mandate to be more proactive in alcohol control. Abstract: Many governments are failing to systematically introduce evidence-based alcohol control policies, and debate continues around issues of market freedom and personal responsibility. The aim of this international study was to assess the extent to which the public considers a range of alcohol control policies to be the responsibility of three different categories of actors: government, the private sector, and individuals. Around 1000 respondents from seven countries (Australia, Canada, China, India, New Zealand, the UK, and the US; n = 7559) completed an online survey assessing demographic characteristics, alcohol consumption status, and perceived responsibility for four alcohol harm-reduction actions relating to alcohol availability, advertising, and public education campaigns. Across the total sample and all assessed actions, governments were selected as an appropriate actor in 66 % of instances, the private sector in 39 %, and individuals in 28 %. Respondents from New Zealand were most likely to consider the actions to be government responsibility and respondents from the US the least. In relatively few instances (8 %), respondents considered the actions unworthy of attention by any actor. Across all seven countries, governments were considered to be the most appropriate actors to undertake actions relating to restricting alcohol availability, regulating alcohol advertising, and disseminating campaigns to educate the public about alcohol-related harm. The results indicate that the public may be receptive to greater intervention in these areas.